(untitled) (Journal of Economic Research & Business Administration, 2017)
In the conditions of the 4th industrial revolution, the role and importance of innovative technology is expanding the practice of commercializing the results of scientific research. This practice is relevant not only for the post-Soviet states, but also for such highly developed countries as Norway, Switzerland, etc. The agenda is not just an innovation infrastructure, but also a commercialization infrastructure. The article examines the state of affairs on granting innovative grants for 2013-2017, analyzes the indicators of the competition for grant financing of commercialization projects for scientific and / or scientific and technical activities. Based on the results of the analysis, the authors propose a number of recommendations.